Akuntabilitas Pengelolaan Dana Desa: Peran Religiusitas, Partisipasi Masyarakat, Komitmen Organisasi Dan Moralitas Perangkat Desa - Asrori, Moh. Ali; Aini, Nurul; Zainuddin, Akhmad (Research Institution and Community Service Universitas Wijaya Kusuma Surabaya, 2024)
This study aims to examine and evaluate the influence of religiosity, community participation, organizational commitment, and morality of village officials on the accountability of village budget management in Kalitengah District, Lamongan Regency. This study used non-probability sampling techniques combined with multiple linear regression analysis. This study used a research sample of 57 village officials, namely the village head, village secretary, and village treasurer who are responsible for administering village finances in Kalitengah sub-district, Lamongan district. The findings of this study explain that religiosity, organizational commitment, and morality of village officials have a significant influence on the accountability of village fund management in Kalitengah District, Lamongan Regency. However, community participation does not have a significant influence on the accountability of village fund management in the sub-district. The findings of this study are expected to provide valuable input for village governments in making decisions about the allocation and use of village funds. In addition, the findings are also expected to be a valuable reference for future researchers in developing their research framework.